2023
DOI: 10.1111/cpr.13423
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and plasticity of epithelial–mesenchymal transition (EMT) in cancer metastasis: Focusing on partial EMT and regulatory mechanisms

Abstract: Epithelial–mesenchymal transition (EMT) or mesenchymal–epithelial transition (MET) plays critical roles in cancer metastasis. Recent studies, especially those based on single‐cell sequencing, have revealed that EMT is not a binary process, but a heterogeneous and dynamic disposition with intermediary or partial EMT states. Multiple double‐negative feedback loops involved by EMT‐related transcription factors (EMT‐TFs) have been identified. These feedback loops between EMT drivers and MET drivers finely regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 166 publications
3
23
0
Order By: Relevance
“…The main therapeutic target of PFD is TGF‐β1, which is the classical EMT promoter. Studies have found that EMT is closely related to tumour metabolism 32,33 . Our experiments showed that PFD inhibited glycolysis in NSCLC cells.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The main therapeutic target of PFD is TGF‐β1, which is the classical EMT promoter. Studies have found that EMT is closely related to tumour metabolism 32,33 . Our experiments showed that PFD inhibited glycolysis in NSCLC cells.…”
Section: Introductionsupporting
confidence: 55%
“…TGF‐β1, the main target of PFD, exerts anti‐inflammatory and anti‐fibrotic effects and plays an important role in regulating key glycolytic enzymes 54,55 . TGF‐β1 participates in the crosstalk between EMT and metabolic reprogramming in cancer progression 32,56–58 . The TGF‐β1 signalling pathway is the primary driver of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that EMT is dynamic and not a binary process, depending on the cell type and tissue type. Complex aspects orchestrate the EMT, including the pretranscriptional level, transcriptional level, posttranscriptional level, translational level, and posttranslational levels 33,34 . Maybe there were posttranscriptional or posttranslational controls behind the AML‐MSC‐regulated EMT‐like program in AML; this needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another phenotypic plasticity process associated with metastasis is the epithelial–mesenchymal transition (EMT). Some tumor cells can reduce adhesion and increase invasiveness through EMT, which helps tumor cells detach from the primary site, and then, this part of the tumor cells can grow at a secondary site through the reverse process of mesenchymal–epithelial transition (MET) . The vasculature not only provides nutrients for tumors but also is a way for tumors to metastasize to distant organs.…”
Section: Introductionmentioning
confidence: 99%
“…Some tumor cells can reduce adhesion and increase invasiveness through EMT, which helps tumor cells detach from the primary site, and then, this part of the tumor cells can grow at a secondary site through the reverse process of mesenchymal−epithelial transition (MET). 11 The vasculature not only provides nutrients for tumors but also is a way for tumors to metastasize to distant organs. The permeability of the vasculature affects the invasion process of the tumor to a large extent.…”
Section: Introduction 1mechanisms and Influencing Factors Of Tumor Me...mentioning
confidence: 99%